Optimization of Microfluidizer-Produced PLGA Nano-Micelles for Enhanced Stability and Antioxidant Efficacy: A Quality by Design Approach - Develi Arslanhan, Esma Nur; Bahadori, Fatemeh; Eskandari, Zahra; Kasapoglu, Muhammed Zahid; Mankan, Erkan (MDPI, 2025)
Introduction: In this study, we aimed to optimize the microfluidizer-based preparation of poly(lactic-co-glycolic acid) nano-micelles (PLGANM), increasingly used for parenteral delivery of poorly water-soluble drugs but typically exhibiting poor physical stability when produced by conventional methods. Method: By systematically tuning microfluidization (MFZ) parameters, we demonstrate an efficient strategy to enhance PLGANM stability and ensure robust, scalable manufacturing, relevant for long-term storage and clinical translation applications. The influence of several key factors designed by Central Composite Design (CCD), including the amount of PLGA and Tween 80, homogenization pressure, and number of passes of MFZ on the size, polydispersity (measured by DLS), and hence stability of the PLGANM, was analyzed for 60 days. 60 PLGANMs produced by the MFZ method (PMFZ) were compared with the PLGANM consisting of equivalent amounts of PLGA and T80 produced using the traditional oil-in-water method (POW). Desired limits were set to minimize standard deviations for Z-average, Zeta Potential, and PDI. Results: Coded variables for optimized PMFZ (OPMFZ) were found to be 82.96 mg PLGA, 6.78 mL 5% T80, 11,000 psi pressure, and 1 pass. Conclusions: This study demonstrates that microfluidization, when guided by a QbD framework, offers precise control over particle attributes and enables reproducible production of stable PLGANM.
Keywords: quality by design; PLGA; hydrophilic; hydrophobic; microfluidizer; stability; antioxidant; DRUG-DELIVERY; NANOPARTICLES; SOLUBILITY; CURCUMIN; MICRO; WATER; ACID; Pharmacology & Pharmacy